2013
DOI: 10.1016/s0140-6736(13)60441-9
|View full text |Cite|
|
Sign up to set email alerts
|

Caesarean section surgical techniques (CORONIS): a fractional, factorial, unmasked, randomised controlled trial

Abstract: SummaryBackground Variations exist in the surgical techniques used for caesarean section and many have not been rigorously assessed in randomised controlled trials. We aimed to assess whether any surgical techniques were associated with improved outcomes for women and babies.Methods CORONIS was a pragmatic international 2×2×2×2×2 non-regular fractional, factorial, unmasked, randomised controlled trial that examined fi ve elements of the caesarean section technique in intervention pairs. CORONIS was undertaken … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(36 citation statements)
references
References 28 publications
1
35
0
Order By: Relevance
“…Since the previous systematic review by Dahlke et al in 2013, the CORONIS trial has reported short-term and long-term data for more than 15,000 women undergoing cesarean delivery randomized to three of five alternative surgical techniques. 4 , 13 15 There was no difference in outcomes related to cesarean delivery surgical technique including long-term outcomes such as subsequent uterine rupture (indicating that double layer uterine closure is not protective) or symptoms attributable to intra-abdominal adhesions (indicating that peritoneal closure is not protective). The authors suggest that in the absence of clinical benefit, considerations such as cost and time savings should dictate appropriate technique.…”
Section: Why Standardize Cesarean Delivery Surgical Technique?mentioning
confidence: 98%
“…Since the previous systematic review by Dahlke et al in 2013, the CORONIS trial has reported short-term and long-term data for more than 15,000 women undergoing cesarean delivery randomized to three of five alternative surgical techniques. 4 , 13 15 There was no difference in outcomes related to cesarean delivery surgical technique including long-term outcomes such as subsequent uterine rupture (indicating that double layer uterine closure is not protective) or symptoms attributable to intra-abdominal adhesions (indicating that peritoneal closure is not protective). The authors suggest that in the absence of clinical benefit, considerations such as cost and time savings should dictate appropriate technique.…”
Section: Why Standardize Cesarean Delivery Surgical Technique?mentioning
confidence: 98%
“…Although there is a paucity of studies, there are examples of well designed and conducted pragmatic RCTs in surgery with appropriate outcome measures (Table 1). There are also examples of trials using composite outcomes combining short-term measures and including some longer-term assessments [24]. However, more high-quality RCTs in surgery are required with better trial design and outcome measures to allow the results to be relevant to routine clinical practice.…”
Section: Challenges For Outcome Measurement In Rcts In Surgerymentioning
confidence: 99%
“…This limits generalisabilityCLASICC Jayne et al 2007 [61]To evaluate the technical and oncological safety and efficacy of laparoscopically assisted surgery for colorectal cancerSeveral were defined:Resection marginsProportion of Dukes’ C2 tumoursIn-hospital mortality3-year overall survival, disease-free survival and local recurrence rates30-Day and 3-month complication ratesTransfusion requirementsHRQL at 2 weeks and 3 months3- and 5-year distant recurrence rates3- and 5-year wound/port site recurrence rates5-year overall survival5-year disease-free survival5-year local recurrenceHRQL at 0.5, 1.5 and 3 yearsN/AN/AThis very pragmatic trial had a sample size selected to provide an overall picture of several short- and long-term outcomes. It was not powered for specific endpointsCORONIS Abalos et al 2013 [24]To assess whether five surgical caesarean techniques were associated with improved outcomes for women and babiesA composite outcome:DeathMaternal infectious morbidity*Further operative proceduresBlood transfusion up to 6-week follow-up visitIndividual components of composite outcomePainInterventions for post-partum haemorrhageStill birthOther severe maternal morbidityApgar score <3 at 5 minLaceration of baby during caesarean sectionDeath of baby at 6 weeksOperation lengthHospital stayAdmission to ITUHospital readmission within 6 weeksAssessed in follow-up study [62]: Reproductive status, subsequent pregnancies, death or serious morbidity of child at 3 yearsWomen’s health and mortality (requested at face to face interview) at 3 yearsN/AN/AMulticentre, multinational pragmatic RCT design. Authors state outcomes were specifically selected to provide guidance for clinical decision-making and composite components were chosen based on primary objective of the trialEVAR Greenhalgh et al 2010 [63]To compare the long-term effects of endovascular and open repair of large aneurysmsAll-cause mortalityAneurysm-related mortality within 30 daysGraft-related complicationsGraft-related interventions30-day operative mortalityHRQL at 1 and 3 monthsGraft-related complicationsGraft-related interventionsAdverse eventsRenal function (up to 8 years)HRQL at 1 yearCost-effectiveness based on QALY (EQ-5D)Resource use annually up to 8 yearsMulticentre pragmatic trial designed to provide long-term data, although HRQL outcomes not measured for duration of trial King et al 2006 [64]To compare short-term outcomes of laparoscopic and open resection of colorectal cancer within an enhanced recovery programmeHospital stayConvalescent hospital stayReadmission hospital stayMajor morbidity † Requirement for opioid analgesiaAntiemetic administrationPerformance indicators for mobility/strength at 2 and 12 days, 6 and 12 weeksSleep and oxygen saturation at 2, 6 12weeksHRQL at 2 and 6 weeksResource use at 2 weeks and 3 monthsN/A…”
Section: Challenges For Outcome Measurement In Rcts In Surgerymentioning
confidence: 99%
“…Currently, hysterectomy constitutes the second most common operation performed in women after cesarean section (CS) [1], which accounts for up to 60 % of deliveries in some countries as estimated by the recent CORONIS trial [4]. In Chile, the current average rate of cesarean section has reached almost 40 %, and it has shown an increasing tendency during recent years [4,5]. Moreover, health system statistics show that even as high as a 70 % of pregnancies are delivered through cesarean section in the private clinical setting [5][6][7].…”
Section: Introductionmentioning
confidence: 99%